(untitled) (BIRDEM Medical Journal, 2017)
A case of dengue virus and chikungunya viruse co-infection is reported here. The patient had fever, severe generalized bodyache, arthritis as well as drowsiness. Laboratory investigations showed dengue-chikungunya co-infection. The objective of our report is to emphasize the co-existence of dengue and chikungunya in a clinical case and to aware the clinicians about chikungunya and dengue co-infection. Birdem Med J 2018; 8(1): 72-74